Integrating Crop Improvement with Resource Management to Alleviate the Effects of Desertification under Climate Change Scenarios - Gowda, C.L Laxmipathi; Kumar, A Ashok; Jamila, P (Annals of Arid Zone, 2016)
Desertification is a serious problem for the drylands affecting the agricultural production and sustainability of ecologies. Climate change further exacerbates this situation, especially in the dry lands of the semi-arid tropics. Climate change predictions point to a warmer world within the next 50 years, a trend that is increasingly being supported by ‘on-the-ground’ measurements. However, the impact of rising temperatures on rainfall distribution patterns in the semi-arid tropics of Africa and Asia remains far less certain. The projected temperature increase and elevated CO2 levels are likely to affect agricultural productivity even under normal rainfall conditions. Scientists at ICRISAT are working towards better understanding of the climate change effects on the crop productivity to develop appropriate crop varieties and crop management technologies, and enabling policies to enhance farmers’ capacity to cope with and adapt to climate change. Climate change effects, particularly temperature increase, affect the crop productivity especially under high-input management. Current research at ICRISAT in developing sorghum, pearl millet, pigeonpea, groundnut and chickpea cultivars adapted to climate change effects is briefly discussed. We believe that a combination of adapted cultivars, improved crop management and natural resource conservation practices, supportive policies and capacity enhancement programs are essential help the farming communities in Asia and sub-Saharan Africa to cope with climate change effects, especially in dryland areas. Key words: Desertification, drylands, semi-arid tropics, climate change, crop adaptation, yield gap, heat and drought tolerance.